FEMA GRAS assessment of natural flavor complexes: Lavender, Guaiac Coriander-derived and related flavoring ingredients. (November 2020) - Fukushima, Shoji; Cohen, Samuel M.; Eisenbrand, Gerhard; Gooderham, Nigel J.; Guengerich, F. Peter; Hecht, Stephen S.; Rietjens, Ivonne M.C.M.; Rosol, Thomas J.; Davidsen, Jeanne M.; Harman, Christie L.; Lu, Vivian; Taylor, Sean V.
Abstract: In 2015, the Expert Panel of the Flavor and Extract Manufacturers Association (FEMA) initiated a program for the re-evaluation of the safety of over 250 natural flavor complexes (NFCs) used as flavor ingredients. This publication, fifth in the series, evaluates the safety of NFCs containing linalool and/or other characteristic mono- and sesquiterpenoid tertiary alcohols and esters using the safety evaluation procedure published by the FEMA Expert Panel in 2005 and updated in 2018. The procedure relies on a complete chemical characterization of the NFC intended for commerce and organization of the chemical constituents of each NFC into well-defined congeneric groups. The safety of each NFC is evaluated using the well-established and conservative threshold of toxicological concern (TTC) concept in addition to data on absorption, metabolism and toxicology of both the constituent congeneric groups and the NFCs. Sixteen NFCs, derived from the Lavandula, Aniba, Elettaria, Daucus, Salvia, Coriandrum, Ribes, Guaiacum/Bulnesia, Citrus, Pogostemon, Melaleuca and Michelia genera, were affirmed as generally recognized as safe (GRAS) under their conditions of intended use as flavor ingredients based on an evaluation of each NFC and the constituents and congeneric groups therein. Highlights: Safety evaluation of natural flavoring ingredients with terpenoid tertiary alcohols . Evaluation used procedure developed by the FEMA Expert Panel for natural flavors . FEMA GRAS status determined/affirmed for 16 natural flavor complexes .